Spectrum of Breast Diseases in Females- a 10 years study - Ahmed, Shakera; Ahmad, Sami; Ahmed, Nadim; Bin Aziz, Nur Mohommad Sayed (Journal of Shaheed Suhrawardy Medical College, 2018)
Objective: To determine the frequency of various breast diseases in female patients. Methodology: This is a prospective (historical)cohort study of female patients from 18 to 55 years of age visiting a female surgeon with breast problems. The study was conducted at Chittagong Metropoliton Hospital and CSCR Hospital in Chittagong over a period of 10 years starting from July 2007 to June 2017. All female patients visiting with breast problems were included in the study, excluding the patients of below 18 years and above 55 years. The findings were tabulated in excel sheet and analyzed for the frequency of each lesion. Results: A total of 3555 patients were included in the study. Benign breast disease (BBD) was much more common than the malignant breast disease which was 3.49% (124/3555) of all breast diseases. Fibroadenoma was the most common benign breast disease, seen in 32.26%(1147/3555) of patients followed by mastalgia, seen in 24.22%(861) patients. The next common breast disease is fibrocystic change in 18.80%(668/3555) patients. Conclusion: Breast diseases, both benign and malignant are the common problems of female. But benign breast diseases are much more common than the malignant diseases. Fibroadenoma is the commonest of all benign breast diseases in our set up. Mastalgia and fibrocystic changes are the next two common diseases. J Shaheed Suhrawardy Med Coll, June 2017, Vol.9(1); 10-12